Dendrimer‐Based Lipid Nanoparticles Deliver Therapeutic FAH mRNA to Normalize Liver Function and Extend Survival in a Mouse Model of Hepatorenal Tyrosinemia Type I. Issue 52 (25th October 2018) - Cheng, Qiang; Wei, Tuo; Jia, Yuemeng; Farbiak, Lukas; Zhou, Kejin; Zhang, Shuyuan; Wei, Yonglong; Zhu, Hao; Siegwart, Daniel J.
Abstract: mRNA‐mediated protein replacement represents a promising concept for the treatment of liver disorders. Children born with fumarylacetoacetate hydrolase (FAH) mutations suffer from Hepatorenal Tyrosinemia Type 1 (HT‐1) resulting in renal dysfunction, liver failure, neurological impairments, and cancer. Protein replacement therapy using FAH mRNA offers tremendous potential to cure HT‐1, but is currently hindered by the development of effective mRNA carriers that can function in diseased livers. Structure‐guided, rational optimization of 5A2‐SC8 mRNA‐loaded dendrimer lipid nanoparticles (mDLNPs) increases delivery potency of FAH mRNA, resulting in functional FAH protein and sustained normalization of body weight and liver function in FAH −/− knockout mice. Optimization using luciferase mRNA produces DLNP carriers that are efficacious at mRNA doses as low as 0.05 mg kg −1 in vivo. mDLNPs transfect > 44% of all hepatocytes in the liver, yield high FAH protein levels (0.5 mg kg −1 mRNA), and are well tolerated in a knockout mouse model with compromised liver function. Genetically engineered FAH −/− mice treated with FAH mRNA mDLNPs have statistically equivalent levels of TBIL, ALT, and AST compared to wild type C57BL/6 mice and maintain normal weight throughout the month‐long course of treatment. This study provides a framework for the rational optimization of LNPs to improve delivery of mRNA broadly and introduces a specific and viable DLNP carrier with translational potential to treat genetic diseases of the liver. Abstract : Structure‐guided, rational optimization of mRNA‐loaded dendrimer lipid nanoparticles (mDLNPs) is conducted to improve mRNA delivery efficacy for therapeutic application. Delivery of luciferase mRNA by mDLNPs in vivo produces 10 7 photons s −1 luminescence at 0.1 mg kg −1 . In a difficult‐to‐treat Hepatorenal Tyrosinemia Type I (HT‐1) mouse model, mDLNPs effectively deliver fumarylacetoacetate hydrolase (FAH) mRNA that normalizes liver function and significantly extends survival.